Diagnostic Value of Magnetic Resonance Imaging (MRI) in Morbidly Adherent Placenta, Taking Surgical Findings as Gold Standard (Medical Forum Monthly, 2020)
Objective: To evaluate the diagnostic accuracy of Magnetic Resonance Imaging in diagnosis of morbidly adherent placenta, comparing with surgical findings.Study Design: Comparative study.Place and Duration of Study: This study was conducted at the Radiology Department of Nishtar Medical Teaching Hospital from Jan, 2019 to Jan. 2020.Materials and Methods: Total 77 patients with clinical suspicion of morbidly adherent placenta having age between 18-38 years were included. Patients with history of more than one cesarean section, antepartum hemorrhage and contra-indications to magnetic resonance imaging were excluded. All the patients were under went MRI pelvis with 1.5 Tesla MRI Achiva scanning system using multiplanner multi-echo imaging. MRI findings were recorded as positive and negative for placenta accreta. MRI findings were correlated with operative findings. Using SPSS-18, data was analyzed and diagnostic accuracy, positive predictive value, negative predictive value, sensitivity and specificity were calculated.Results: 77 patients were included in study according to inclusion criteria. Patients mean age was 26.95±4.05 years. MRI was true positive for 25 and false positive for 3 patients. True negatives were 19 and false negative were only 3 patients. Diagnostic accuracy, positive predictive value (PPV), negative predictive value (NPV), sensitivity and specificity of MRI were 87.01%, 88.37%, 85.29 %, 88.37%, and 85.29% respectively.Conclusion: MRI is a new non-invasive diagnostic modality with significantly high accuracy in diagnosis of morbid adherence of placenta.